PROBLEMS OF SIZE OPTIMIZATION OF FLEXIBLE TANKS FOR FUEL FARMS - Yu. N. Ribakov; S. V. Larionov; S. I. Chirikov; R. I. Kyunnap (Научный вестник МГТУ ГА, 2016)
The article outlines the theoretical approaches to the optimization of the geometrical parameters of flexible tanks for petroleum products taking into account the total length of the stitches on the top and bottom surfaces. The algorithm, mathematical models and optimization criterion to significantly (up to 20%) increase the efficiency of cutting the material of construction are proposed. On the basis of these curves are the formulas for determining the optimal height, length and width of the flexible container. The calculations are for the optimal sizes for example, flexible container with a capacity of 250 m3.